Mass Certification Policy for Community Land Objects - Suwardi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Public Service Policy for Land Certification can be said to be a new breakthrough in the field of public services, because the method used to provide services is by visiting the community. The community will be served at a place agreed upon by the local land office and sub-district office. In general regarding land registration, the government has issued Government Regulation Number 24 of 1997 concerning Land Registration. This government regulation is a refinement of Government Regulation Number 10 of 1961. Furthermore, technically the rules for implementing land registration refer to the Regulation of the Minister of State for Agrarian Affairs/Head of BPN Number 3 of 1997 concerning Provisions for Implementing Government Regulation Number 24 of 1997 concerning Land Registration. Other regulations to strengthen the implementation of the People's Service Policy for Land Certification are Government Regulation Number 46 of 2002 concerning Tariffs for Types of Non-Tax State Revenue Applicable to the National Land Agency and Decree of the Head of the National Land Agency of the Republic of Indonesia Number 24 of 2008 concerning the Establishment of Implementers of Development and Development Activities. Monitoring Larasita Activities. This was then followed up by the Regulation of the Head of the National Land Agency of the Republic of Indonesia Number 18 of 2009 concerning Larasita of the National Land Agency of the Republic of Indonesia